Automated Machine Learning & Tuning with FLAML - Wang, Chi; Wu, Qingyun; Liu, Xueqing; Quintanilla, Luis (ACM SIGKDD Conference on Knowledge Discovery and Data Mining (KDD 2022), 2022)
In this tutorial, we will provide an in-depth and hands-on tutorial on Automated Machine Learning & Tuning with a fast python library FLAML. We will start with an overview of the AutoML problem and the FLAML library. In the first half of the tutorial, we will then give a hands-on tutorial on how to use FLAML to automate typical machine learning tasks in an end-to-end manner with different customization options and how to perform general tuning tasks on user-defined functions. In the second half of the tutorial, we will introduce several advanced functionalities of the library. For example, zero-shot AutoML, fair AutoML, and online AutoML. We will close the tutorial with several open problems, and challenges learned from AutoML practice.